Industrial carnallite-waste for thermochemical energy storage application. (1st May 2020) - Mamani, V.; Gutiérrez, A.; Fernández, A.I.; Ushak, S.
Highlights: The reuse of potassium carnallite-waste for thermochemical heat storage was studied. Carnallite-waste compared to the synthetic material showed a low cyclic stability. Waste material was optimized under seasonal pressure and temperature conditions. Optimal results during 10 cycles of dehydration at 4.0 kPa and 110 °C were obtained. Abstract: The key to successful development and implementation of thermochemical storage systems is the identification of high energy density and low-cost storage materials. In this work, an industrial waste based on a double salt hydrate, coming from non-metallic mining was studied for thermochemical storage applications. Initially, chemical characterization was performed and determined that carnallite-waste material consists of 73.54 wt% of KCl·MgCl2 ·6H2 O and impurities such as NaCl (23.04 wt%), KCl (1.76 wt%) and CaSO4 (1.66 wt%). Using thermal analyses methods, the operating conditions such as temperatures and partial pressures, were optimized for seasonal thermochemical storage applications to PHy  = 1.3 kPa and ϑHy  = 40 °C, and to PDe  = 4.0 kPa and ϑDe  = 110 °C. Under these conditions, the reaction reversibility over 10 cycles (10 years) was significantly high, with only 8.5% decrease in chemical reversibility. Furthermore, the duration of dehydration and hydration isotherms was optimized to 15 and 360 min, respectively. Finally, 1.129 GJ/m 3 energy storage density was calculated after the tenth cycle of hydration/dehydration for this material. Hence 7.1 m 3 of carnallite was estimated to meet the demand of 8 GJ of energy for an average household during the six months of cold seasons. These results are comparable and competitive with an energy storage density of materials such as K2 CO3 and MgCl2, reported as promising for seasonal thermochemical storage applications. It should be noted that carnallite-waste material has no commercial value so far and its use contributes to developing sustainable low-cost thermochemical energy storage systems.